2020
DOI: 10.1093/mnras/staa714
|View full text |Cite
|
Sign up to set email alerts
|

Semi-analytic forecasts for JWST – III. Intrinsic production efficiency of Lyman-continuum radiation

Abstract: The James Webb Space Telescope (JWST ) is expected to enable transformational progress in studying galaxy populations in the very early Universe, during the Epoch of Reionization (EoR). A critical parameter for understanding the sources that reionized the Universe is the Lyman-continuum production efficiency, ξ ion , defined as the rate of production of ionizing photons divided by the intrinsic UV luminosity. In this work, we combine self-consistent star formation and chemical enrichment histories predicted by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 98 publications
(134 reference statements)
6
15
0
Order By: Relevance
“…Yung et al (2020) developed a semi-analytic approach with a Chabrier IMF and compared their results with previous studies, including the hydrodynamic simulations presented in Wilkins et al (2016). They found that ξ ion was nearly unaffected by the change from Chabrier to Salpeter IMF [52]. Despite the different IMF, also their values agree with our fiducial ξ ion = 10 25.2 Hz/erg assumption.…”
Section: Reionization With Galaxies Only 431 Implications On F Escsupporting
confidence: 83%
See 3 more Smart Citations
“…Yung et al (2020) developed a semi-analytic approach with a Chabrier IMF and compared their results with previous studies, including the hydrodynamic simulations presented in Wilkins et al (2016). They found that ξ ion was nearly unaffected by the change from Chabrier to Salpeter IMF [52]. Despite the different IMF, also their values agree with our fiducial ξ ion = 10 25.2 Hz/erg assumption.…”
Section: Reionization With Galaxies Only 431 Implications On F Escsupporting
confidence: 83%
“…Finally, Eldridge et al (2017) demonstrated that ξ ion is sensitive to variation in the upper end of the stellar IMF. In particular, they highlighed a lower photon production efficiency in IMF with power law slope extended up to 100 M with respect to similar models extended up to 300 M [52,55]. These evaluations lead us to neglect the variations induced on ξ ion by the IMF.…”
Section: Reionization With Galaxies Only 431 Implications On F Escmentioning
confidence: 86%
See 2 more Smart Citations
“…This feature makes Santa Cruz SAM particularly suitable for ISM line emission predictions. The SFR, stellar mass, cold gas mass, and other predictions of the Santa Cruz SAM have been shown to be broadly consistent with observations from the local universe to z ∼ 10 ( Popping et al 2014b;Yung et al 2019aYung et al , 2019bYung et al , 2020aYung et al , 2020bSomerville et al 2021).…”
Section: Santa Cruz Semianalytic Modelsupporting
confidence: 76%